Quantitative restrictions on the flow of narcotics: Supply and demand restraints in a north-south macro-model - S. Mansoob Murshed (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This paper constructs a macroeconomic model of North-South interaction where the flow of narcotics from the South to the North is restricted. Their economic effects are akin to quantitative restrictions in trade policy. Two alternative policy scenarios will be considered. One involves reducing the supply of drugs at source, accompanied by aid. Supply side restrictions have negative aggregate supply side effects in the producing region, because of the monopoly rents generated from that type of control. This makes them a second best policy, particularly if the accompanying aid is not used for poverty alleviation and fails to expand domestic aggregate demand. Alternative, demand side restrictions will be found to be superior.
Keywords: D74; F02; F41; 330; North-South interaction; trade policy; narcotics control; Droge; Nord-Süd-Beziehungen; Theorie